Heathers : the musical : vocal selections - Murphy, Kevin, 1967-; O'Keefe, Laurence; Waters, Daniel (Samuel French, 2018)
"Transformed from a cult movie into cult hit musical, Heathers, the musical takes you back to 1980s Westerberg High where the powerful and ruthless clique, the Heathers, rule the school."--back cover.